LARANGAN PEMBATASAN KUANTITATIF: STUDI KASUS INDONESIA –IMPORTATION OF HORTICULTURALPRODUCTS, ANIMALS AND ANIMAL PRODUCTS - Rizky, Faiz Muhammad; Velentina, Rouli Anita (Jurnal Hukum & Pembangunan, 2021)
n 2014, Indonesia implemented measures relating to the importation of horticultural products,animals, and animal products which were seen as a trade barrier in the form of quantitative restrictions imposed through the import licensing system. This article analyzes whether the paneland appellate body decision in the case of Indonesia -Importation of Horticultural Products, Animals and Animal Products under the provisions contained in the WTO legal framework. Indonesias policies cannot be justified under WTO legal framework, thoughthere are some exceptions to the quantitative restriction provision.